Incidence, clinical manifestations and clipping of nail psoriasis in the dermatology center of the Hospital Universitário Evangélico de Curitiba - Garbers, Luiz Eduardo Fabricio de Melo (2016)
Background: Psoriasis is a chronic inflammatory skin disease that often progresses with nail alterations. It is suspected that there is a correlation between nail psoriasis and enthesitis of the distal interphalangeal joint, seeming to serve as a predictor. O b jectives: To analyze the profile of patients with nail psoriasis and correlate the presence of nail alterations with psoriatic arthritis, quality of life, extent of psoriasis and the histopathology of the nail. Methods: An observational cross-sectional study with 40 patients with a diagnosis of psoriasis and without systemic treatment. The patient profile was researched, including quality of life and evaluated for the presence of psoriatic arthritis. The severity of the skin psoriasis and the presence of nail lesions were evaluated. Nail fragments were collected and analyzed through clipping. It obtained 100% of positivity for psoriasis in the histopathology exam of the nail plate. R esults: Of the 40 patients, 65% were diagnosed with nail psoriasis. Suggestive findings of psoriatic arthritis in hands were present in 33%, being more frequent in those with nail alteration (p = 0.01). In 92.3% of patients diagnosed with psoriatic arthritis in the hands there was some nail injury. The most frequent injuries were pitting and onycholysis. C onclusions: Patients with nail psoriasis are usually men, with worse quality of life and higher chance of psoriatic arthritis. The correlation between the nail involvement of psoriasis and psoriatic arthritis in hands confirms the association between these two forms. The clinical diagnosis of nail psoriasis did not correlate with the histological diagnosis.